2023
DOI: 10.1111/icad.12703
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation drives inter‐ and intraspecific variation in flight‐related morphological traits of aquatic insects at different landscape scales

Wenfei Liao,
Hao Lin

Abstract: Urbanisation, as an unstoppable global phenomenon, has led to decreasing connectivity between habitats, which gives strong pressure on organisms. Current research has barely investigated urban effects on aquatic insect species traits. Here, we investigated how inter‐ and intraspecific variations of flight‐related morphological traits change along an urban gradient in three species of Dytiscidae at different landscape scales. We collected specimens in 30 urban wetlands in Helsinki, Finland. We measured flight‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…Insects are extremely diverse, both functionally and taxonomically, and have complex life histories (Schmitt & Burghardt, 2021), making it difficult to discover which traits determine if an insect species will be an urban exploiter or avoider. Determining the scale at which insect species and populations respond to urbanisation is a fundamental pursuit of the landscape ecology of insects (Betts et al 2019), and previous studies have demonstrated the spatial scale at which insects respond to urbanisation differs across taxonomic and functional groups (Chust et al, 2004;González-Césped et al, 2021;Liao & Lin, 2024). Our approach, which tested urbanisation effects on multiple insect orders at a uniform spatial scale, may have missed crucial interactions between traits and urbanisation operating at either smaller or larger spatial scales than examined.…”
Section: The Challenge Of Finding Generalizable Traits Leading To Urb...mentioning
confidence: 99%
“…Insects are extremely diverse, both functionally and taxonomically, and have complex life histories (Schmitt & Burghardt, 2021), making it difficult to discover which traits determine if an insect species will be an urban exploiter or avoider. Determining the scale at which insect species and populations respond to urbanisation is a fundamental pursuit of the landscape ecology of insects (Betts et al 2019), and previous studies have demonstrated the spatial scale at which insects respond to urbanisation differs across taxonomic and functional groups (Chust et al, 2004;González-Césped et al, 2021;Liao & Lin, 2024). Our approach, which tested urbanisation effects on multiple insect orders at a uniform spatial scale, may have missed crucial interactions between traits and urbanisation operating at either smaller or larger spatial scales than examined.…”
Section: The Challenge Of Finding Generalizable Traits Leading To Urb...mentioning
confidence: 99%
“…Urban density may also select for dispersal-enhancing morphologies within populations or species assemblages, which has been proposed for flight-related traits of aquatic beetles (Liao & Lin, 2024), as well as body size of wild bees (Brasil et al, 2023) and macro moths (Merckx, Kaiser, & Van Dyck, 2018). These patterns, which are also considered a form of ecological filtering, may reflect changes in the costs and benefits of dispersal in urban environments (Ancillotto & Rocco, 2024;Jones & Leather, 2012), although they may also reflect traits of founder individuals in low-dispersal systems, and conclusions are largely uncertain (see also genetics section below) (Federico et al, 2024).…”
Section: Uhi Effectmentioning
confidence: 99%
“…Lessons from metapopulation ecology and a better understanding of patch quality for specific taxa will be critical to raising urban insect diversity and conserving this as a stable ecosystem component (e.g., Azhar et al, 2024;Liao & Lin, 2024). There are pathways to understanding patch improvement, but above this, integrating connectivity and opportunity for insects in urban areas more broadly and by design will contribute further (e.g., Noël et al, 2024) as will translocations to restore extirpated diversity (e.g., Yagui et al, 2024).…”
Section: In Summarymentioning
confidence: 99%
See 1 more Smart Citation